Consecutive-Type Reliability Systems: An Overview and Some Applications. (31st May 2015) - Triantafyllou, Ioannis S.
Abstract : The family of consecutive-type reliability systems is under investigation. More specifically, an up-to-date presentation of almost all generalizations of the well-known consecutivek -out-of-n :F system that have been proposed in the literature is displayed, while several recent and fundamental results for each member of the aforementioned family are stated.